Issues of Type 2 Diabetes Disease Effective Treatment in Kazakhstan - N.T. Ablaikhanova; A.Y. Yessenbekova; Tazhiyeva Aigul; Z.B. Yessimsiitova; A.K. Saidakhmetova; A.E. Malibayeva; B.J. Sanbaeva; M. Molsadykkyzy (Journal of Pharmacy and Nutrition Sciences, 2020)
In his address to the people, the First President of our country, emphasized the need to introduce innovative methods of treating socially significant diseases. Among these diseases, diabetes holds a special position. More than 14,000 new cases of diabetes mellitus are officially detected annually in Kazakhstan. The real picture of the disease is difficult to compare with these data. This review discusses the prevalence of type 2 diabetes among the population of the Republic of Kazakhstan, and the causing factors such as age, race, genetic predisposition (OR = 3), obesity, glucose level and total cholesterol etc. It was found that the main complications and concomitant diseases of diabetes in residents of different regions are polyneuropathy - 22.4%, diabetic retinopathy - 14%, diabetic foot syndrome - 13.6%, arterial hypertension - 13.6% and coronary heart disease (CHD) - 14.4%. Only 1.8% of the population is diagnosed with type 2 diabetes, latent manifestations of type 2 diabetes mellitus, one in four people in Kazakhstan can be sick, 38% of adults aged 20-79 suffer from prediabetes, and 8.2% with diabetes. It is believed that by 2030 in Kazakhstan, there may be about a million patients with diabetes. Diabetes mellitus, in accordance with the Code of the Republic of Kazakhstan “On the health of the people and the health care system” belongs to the category of socially significant diseases. Therefore, the study of type 2 diabetes is one of the urgent problems of the public health in Kazakhstan.